PERBEDAAN KONFORMITAS DITINJAU DARI LOCUS OF CONTROL PADA REMAJA SISWA-SISWI KELAS UNGGULAN SMA DWI WARNA MEDAN - Mardianri Mardianri; Laili Alfita (Faculty of Psychology, Universitas Medan Area, 2015)
This study aimed to determine differences in terms of conformity of Locus Of Control adolescent high school students in SMK DwiWarna Medan. This study used comparative quantitative research methods. Data collection techniques used in this study, using a scale of Locus Of Control and Conformity Scale which has been tested for validity and reliability. The results showed that there were differences between Locus Of Control against conformity (F = 32.608, p <0.000). Thus it can be said when Locus Of Control, the internal low conformity. Meanwhile, when Locus Of Control Externally, the high conformity in SMA featured DwiWarna Medan. Another result is internal Locus Of Control (ME = 17.706, MH = 27), whereas the external Locus Of Control (ME = 21.260, MH = 27). Conformity in this study were moderate (ME = 19.1379, MH = 18).Keyword: Comformity, Locus Of Control